Socialization on the Utilization of Pineapple as a Natural Source of Antioxidants to Support Health Productive Age Communities in West Bangkok Gurah Kediri - Winartiana; Prayoga Fery Yuniarto; Okky Intan Mawarni (Universitas STRADA Indonesia, 2026)
Exposure to external free radicals—such as pollution, ultraviolet radiation, and smoking-can trigger oxidative stress, which plays a role in the development of various degenerative diseases, including heart disease and cancer. Essential preventive efforts can be made by increasing the consumption of natural foods rich in antioxidants. Pineapple (Ananas comosus), as a local commodity, is known to contain high antioxidant levels that can help neutralize free radicals. This community service activity aimed to improve the knowledge and understanding of residents in Dusun Bangkok Barat, Gurah, Kediri regarding the dangers of free radicals, their health impacts, and the benefits of pineapple as a natural source of antioxidants. The program used a one-group pretest–posttest design involving 32 respondents. Respondents consisted of residents of Bangkok aged 18–55 years who had previously consumed pineapple and were willing to participate by completing the questionnaire. The intervention consisted of a health education session conducted on July 18, 2025. The session was delivered through a lecture and a question-and-answer discussion using PowerPoint presentation slides. Educational pamphlets were distributed to participants, and questionnaires were administered to assess participants knowledge before and after the session. Data analysis showed a significant increase in knowledge across all measured aspect such as knowledge regarding free radicals, antioxidants, pineapple, as well as community perceptions and habits. The average improvement in correct responses between the pre-test and post-test exceeded 40%, with the highest increase (57%) seen in understanding the sources of free radicals. Additionally, respondents’ belief in the benefits of pineapple rose to 97%, and 88% expressed an intention to increase their consumption of antioxidant-rich fruits after attending the session. The program proved effective in improving knowledge, shifting perceptions, and encouraging positive behavioral intentions. These findings highlight the potential of community health education based on local commodities, such as pineapple, as an effective and sustainable preventive strategy.